PkM Olahan Pangan Hortikultura di Kelompok Wanita Tani Desa Tesbatan - Eny Idayati; Ayu Pramita; Kartiwan Kartiwan (Madani : Indonesian Journal of Civil Society, 2021)
The Community Partnership Program (PKM) activity in the Tesbatan Village Women's Group aims to exploit local potential, namely moringa leaves, corn, chili, tomatoes, papaya and coconut. The local potentials are processed into nutritional products with long shelf life. Thus it will increase the income and health of partner families. Partners are trained and assistanced during the processing practice of tea products, noodles, moringa cake, corn tortillas, VCO, and sukade. The training was conducted in groups with the andragogy approach that was presented with a ratio of 30% theory and 70% practice. The implementation of PKM has provided training participants with knowledge about cassava diversification, packaging and labeling. The main target of assistance to farmer groups is to enable the group to independently produce processed products as to increase nutritional and economic value by being marketed around the partner group's residence so that they can continue to carry out housework. In addition to the activities of processed local products, counseling was also carried out about the urgency of stunting on adolescent women and their effects on future generations. Partners are also equipped with knowledge about packaging and label design for the products. The activity received a very good response, this can be seen from the involvement of partners during the PKM, as well as a positive attitude and high motivation throughout the series of activities indicated by the presence and interest of partners in every discussion, training, and monitoring activity.